Harry Potter and the Chamber of Secrets - Rowling, J. K. (Bloomsbury London, 2000)
The three firm friends, Harry, Ron and Hermione, are soon immersed in the daily round of Potions, Herbology, Charms, Defence Against the Dark Arts, and Quidditch. But then horrible and mysterious things begin to happen. Harry keeps hearing strange voices, sinister and dark messages appear on the wall, and then Ron's sister Ginny disappears...